Haven: Sharing receptive music listening to foster connections and wellbeing for people with dementia who are nearing the end of life, and those who care for them. (July 2020) - Garabedian, Claire E; Kelly, Fiona
This paper reports on research exploring the effects of music played for 12 dyads: a care home resident ('resident') with dementia and someone closely connected to him/her ('carer'). Six individualised music interventions (3 live and 3 pre-recorded) were played by the first author on solo cello within five Scottish non-NHS care homes. All interventions were video-recorded. Semi-structured interviews with carer participants, key staff, and managers explored their responses to interventions. Thick descriptions of video recordings and interview transcripts were thematically coded using Nvivo. A key finding was that structural elements of the interventions combined with characteristics of the music played facilitated an internalised experience of 'haven'; sonically transporting listeners away from their present reality and fulfilling the basic human needs for inclusion, comfort, identity, occupation and attachment.